2022
DOI: 10.3390/ejihpe12030022
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Balanced Time Perspective: Predictive Model of Psychological Well-Being and Gender Differences in College Students

Abstract: Background: The aims of the study were to establish an adjustment model to analyze the relationship among mindfulness, balanced time perspective (BTP) and psychological well-being (PWB) in college students and to explore gender differences among the variables. Method: The sample consisted of 380 college students, 220 women and 160 men, uniformly distributed according to the university’s faculties. Results: The results indicate that the synergy between mindfulness and BTP predicts the variance of PWB by 55%. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…Nonetheless, this pattern appears to be affected by mindfulness-based traits. A recent study reported a stronger connection between a balanced time perspective, mindfulness-related traits and psychological well-being among a sample of female, compared to male, college students [ 75 ]. In light of this evidence, we suggest that despite males being possibly more prone to the salience of the present moment compared to females, increasing their expertise in mindfulness and/or meditation techniques that adopt awareness-based features could potentially help female practitioners in becoming more prone to the present.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this pattern appears to be affected by mindfulness-based traits. A recent study reported a stronger connection between a balanced time perspective, mindfulness-related traits and psychological well-being among a sample of female, compared to male, college students [ 75 ]. In light of this evidence, we suggest that despite males being possibly more prone to the salience of the present moment compared to females, increasing their expertise in mindfulness and/or meditation techniques that adopt awareness-based features could potentially help female practitioners in becoming more prone to the present.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding recommendations for cancer care, it appears that time perspectives among cancer patients are disproportionate and somehow stiffened. This is potentially of great importance since balanced and proportionately developed perspectives, including the ability to flexibly switch between them, are considered a predictor of well-being ( Fuentes et al, 2022 ). Results of this study indicate that the space of possible therapeutic intervention concerns present hedonism and transcendental future.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding future directions, several factors exist that could potentially influence TP, acculturative stress and coping. Some of these other factors include well-being, life satisfaction, and mindfulness, among many others (Fuentes et al, 2022;Olivera-Figueroa et al, 2016. Nonetheless, these factors were not measured on this study, which by design was focused on the constructs of TP, acculturative stress and coping strategies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%